From colonial policy to national treasure tracing the making of audiovisual heritage in the Philippines - Patino, Bernadette Rose Alba (2018)
Access online through this link: https://www.plarideljournal.org/article/from-colonial-policy-to-national-treasure-tracing-the-making-of-audiovisual-heritage-in-the-philippines
Keywords: Audiovisual materials; Audiovisual archives; Motion pictures